2016
DOI: 10.1590/1981-6723.1016
|View full text |Cite
|
Sign up to set email alerts
|

Obtenção e caracterização de farinha de casca de uva e sua utilização em snack extrusado

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado. Obtenção e caracterização de farinha de casca de uva e sua utilização em snack extrusado Obtention and characterization of grape skin flour and its use in an extruded snack ResumoEste estudo propôs caracterizar a farinha de casca de uva (FCU) e o efeito de sua inclusão em snack ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
3
8
0
17
Order By: Relevance
“…Oliveira et al [54] conducted a study investigating the partial substitution of corn grits by grape waste flour (peels and seeds) using the 9-point Hedonic Scale for checking the acceptance, and discovered a better acceptance for the formulations containing, 15% and 20% (in order of preference), which also offered the highest fibre content. Another investigation of grape waste flour (peels) showed that the Global Acceptance Test disclosed that the extrudate containing 5% of this flour had better acceptance than the control formulation and the 10% formulation (regarding the texture parameter), and was not different from the control formulation in terms of flavour [55].…”
Section: Sensory Analysis Of Cake Formulationsmentioning
confidence: 99%
“…Oliveira et al [54] conducted a study investigating the partial substitution of corn grits by grape waste flour (peels and seeds) using the 9-point Hedonic Scale for checking the acceptance, and discovered a better acceptance for the formulations containing, 15% and 20% (in order of preference), which also offered the highest fibre content. Another investigation of grape waste flour (peels) showed that the Global Acceptance Test disclosed that the extrudate containing 5% of this flour had better acceptance than the control formulation and the 10% formulation (regarding the texture parameter), and was not different from the control formulation in terms of flavour [55].…”
Section: Sensory Analysis Of Cake Formulationsmentioning
confidence: 99%
“…Marselan (V. vinifera) was carried out to evaluate the effect of its inclusion in extruded snack with respect to nutritional, technological, and sensory parameters [22]. The microbiological determinations of coliforms at 45°C and Salmonella in the flours were also performed.…”
Section: Composition Of Grapes Pomace and Its Potential For Usementioning
confidence: 99%
“…The fiber formulation containing 9% (5% fiber) of flour presented better acceptance results with regard to color, aroma, and texture attributes compared to the standard snack formulation. According to these authors [22], for the nutritional enrichment (fibers and phytochemicals) and for adding value to the agro-industrial residue discarded by the wineries, the addition of pomace flour in extruded snacks is viable and quite interesting.…”
Section: Composition Of Grapes Pomace and Its Potential For Usementioning
confidence: 99%
“…Elaborou-se um mix de farinhas com amido de milho, farinha de uva e linhaça dourada. A porcentagem de linhaça dourada foi fixa enquanto a porcentagem de farinha de uva e amido variou, conforme Tabela 1, com a concentração de farinha de uva obtida por meio de estudos (ACUN;GÜL, 2014;BENDER et al, 2016;DIETTRICH;BAUER; As temperaturas de assamento foram 140, 160 e 180 °C, sendo prédeterminadas experimentalmente. O experimento foi analisado por um planejamento experimental, os experimentos foram delineados inteiramente ao acaso com esquema fatorial 2 2 , com adição de três repetições no ponto central, totalizando 7 ensaios, conforme demonstrado nas Tabelas 2 e 3.…”
Section: Materiais E Métodosunclassified